Resveratrol has anti-thyroid effects both in vitro and in vivo. (September 2017) - Giuliani, Cesidio; Iezzi, Manuela; Ciolli, Laura; Hysi, Alba; Bucci, Ines; Di Santo, Serena; Rossi, Cosmo; Zucchelli, Mirco; Napolitano, Giorgio
Abstract: Resveratrol is a natural polyphenol with antioxidant, anti-inflammatory, and antiproliferative properties. We have shown previously that resveratrol decreases sodium/iodide symporter expression and iodide uptake in thyrocytes, both in vitro and in vivo . In the present study, we further investigated the effects of resveratrol, with evaluation of the expression of additional thyroid-specific genes in the FRTL-5 rat thyroid cell line: thyroglobulin, thyroid peroxidase, TSH receptor, Nkx2-1, Foxe1 and Pax8. We observed decreased expression of these genes in FRTL-5 cells treated with 10 μM resveratrol. The effects of resveratrol was further evaluated in vivo using Sprague-Dawley rats treated with resveratrol 25 mg/kg body weight intraperitoneally, for 60 days. No clinical signs of hypothyroidism were seen, although the treated rats showed significant increase in thyroid size. Serum TSH and thyroid hormone levels were in the normal range, with significantly higher TSH seen in resveratrol-treated rats, compared with control rats. Histological and immunohistochemical analyses confirmed increased proliferative activity in the thyroid from resveratrol-treated rats. These data suggest that resveratrol acts as a thyroid disruptor and a goitrogen, which indicates the need for caution as a supplement and for therapeutic uses. Highlights: Resveratrol acts as a thyroid disruptor with anti-thyroid and goitrogenic effects. Resveratrol decreases expression of thyroid-specific genes involved in thyroid growth and function. Long-term treatment with resveratrol has goitrogenic effects in Sprague-Dawley rats.